Preliminary assessment of anti-α-Gal IgG and IgM levels in patients with patent Plasmodium vivax infection - Zélia Barbosa de Almeida Coelho; Luiza Carvalho Mourão; Beatriz Carolina Medeiros Rodrigues; Gustavo Pereira Cardoso-Oliveira; Robert Hincapie; Carlos Sanhueza-Chavez; MG Finn; Cor Jesus Fernandes Fontes; Alexandre Ferreira Marques; Érika Martins Braga (Memorias do Instituto Oswaldo Cruz)
Anti-α-Gal responses may exert a protective effect in falciparum malaria. However, the biological role of such antibodies is still unknown during Plasmodium vivax infections. We investigated IgG and IgM responses to α-Gal in individuals with vivax malaria. Anti-α-Gal IgG and IgM levels were higher in these patients than in controls, but no significant correlation was found between parasitaemia and anti-α-Gal response, nor between this response and ABO blood group status. This is the first study to investigate anti-α-Gal antibodies in P. vivax-infected patients; a larger survey is necessary to achieve a better understanding of host immune response during vivax malaria.